2004
DOI: 10.1101/gad.1149604
|View full text |Cite
|
Sign up to set email alerts
|

Rad6 plays a role in transcriptional activation through ubiquitylation of histone H2B

Abstract: Covalent modifications of the histone N tails play important roles in eukaryotic gene expression. Histone acetylation, in particular, is required for the activation of a subset of eukaryotic genes through the targeted recruitment of histone acetyltransferases. We have reported that a histone C tail modification, ubiquitylation of H2B, is required for optimal expression of several inducible yeast genes, consistent with a role in transcriptional activation. H2B was shown to be ubiquitylated and then deubiquityla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
191
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(206 citation statements)
references
References 67 publications
13
191
0
2
Order By: Relevance
“…We examined galactose-mediated induction of the GAL10 gene ( Figure 5A). Consistent with previous reports (Henry et al, 2003;Kao et al, 2004), we found that the K123R mutation reduced GAL10 induction about threefold. Under identical conditions, however, the K123ϩ mutant showed little if any induction of GAL10, arguing that other lysine residues within H2B (besides K123) are important for GAL activation.…”
Section: Ubiquitylation Of Lysine 123 Of H2b Can Be Essentialsupporting
confidence: 82%
See 1 more Smart Citation
“…We examined galactose-mediated induction of the GAL10 gene ( Figure 5A). Consistent with previous reports (Henry et al, 2003;Kao et al, 2004), we found that the K123R mutation reduced GAL10 induction about threefold. Under identical conditions, however, the K123ϩ mutant showed little if any induction of GAL10, arguing that other lysine residues within H2B (besides K123) are important for GAL activation.…”
Section: Ubiquitylation Of Lysine 123 Of H2b Can Be Essentialsupporting
confidence: 82%
“…Yeast deleted for RAD6 or BRE1, or carrying the K123R H2B mutant, display reduced GAL gene activation (Kao et al, 2004), as well as defects in meiosis (Robzyk et al, 2000;Yamashita et al, 2004), gene silencing (Dover et al, 2002;Sun and Allis, 2002), and histone H3 methylation (Dover et al, 2002;Sun and Allis, 2002), but are nonetheless viable. Our finding that there are multiple ubiquitylation events on histone H2B raises the important point that previous analyses of the functional consequences of Rad6 -Bre1-dependent H2B ubiquitylation (at K123) have been performed within a backdrop of other H2B-ubiquitylation events, which in turn may mask effects resulting from loss of Rad6 -Bre1 ubiquitylation.…”
Section: Ubiquitylation Of Lysine 123 Of H2b Can Be Essentialmentioning
confidence: 99%
“…Moreover, Minsky et al [53] demonstrated that H2Bub is selectively associated with the transcribed regions, but not the promoters, of expressed genes. These observations do not necessarily imply an active role for H2Bub in mammalian transcription regulation; nevertheless, such a role can be deduced from earlier studies in the budding yeast, where the use of strains harboring a point mutation in the ubiquitylation site of H2B revealed the direct involvement of H2Bub in transcriptional regulation [40,58,59].…”
Section: Monoubiquitylated Histone H2bmentioning
confidence: 90%
“…Monoubiquitylated histone H2B: from general to highly specific transcription regulator Ubiquitylation of histone H2B in mammalian cells was identified over three decades ago [37], but more than two decades passed before the function of this modification in regulating mammalian chromatin-associated processes was deciphered. The first breakthrough came with the identification of the budding yeast protein Bre1 [38,39], which, together with the ubiquitin-conjugating enzyme Rad6, serves as the E3 ligase in the monoubiquitylation of the yeast histone H2B on lysine 123 (K123) within transcribed chromatin [38][39][40][41]. Notably, H2B monoubiquitylation was subsequently found to be required for di-and trimethylation of lysine 4 and lysine 79 of histone H3 at transcribed chromatin [42][43][44][45][46][47][48].…”
Section: Open Access Under CC By-nc-nd Licensementioning
confidence: 99%
See 1 more Smart Citation